Correlations between Photodegradation of Bisretinoid Constituents of Retina and Dicarbonyl Adduct Deposition - Zhou, Jilin (J Biol Chem, 2015)
Non-enzymatic collagen cross-linking and carbonyl adduct deposition are features of Bruch's membrane aging in the eye, and disturbances in extracellular matrix turnover are considered to contribute to Bruch's membrane thickening. Because bisretinoid constituents of the lipofuscin of retinal pigment epithelial (RPE) cells are known to photodegrade to mixtures of aldehyde-bearing fragments and small dicarbonyls (glyoxal (GO) and methylglyoxal (MG)), we investigated RPE lipofuscin as a source of the reactive species that covalently modify protein side chains. Abca4(−/−) and Rdh8(−/−)/Abca4(−/−) mice that are models of accelerated bisretinoid formation were studied and pre-exposure of mice to 430 nm light enriched for dicarbonyl release by bisretinoid photodegradation. MG protein adducts were elevated in posterior eyecups of mutant mice, whereas carbonylation of an RPE-specific protein was observed in Abca4(−/−) but not in wild-type mice under the same conditions. Immunolabeling of cryostat-sectioned eyes harvested from Abca4(−/−) mice revealed that carbonyl adduct deposition in Bruch's membrane was accentuated. Cell-based assays corroborated these findings in mice. Moreover, the receptor for advanced glycation end products that recognizes MG and GO adducts and glyoxylase 1 that metabolizes MG and GO were up-regulated in Abca4(−/−) mice. Additionally, in acellular assays, peptides were cross-linked in the presence of A2E (adduct of two vitamin A aldehyde and ethanolamine) photodegradation products, and in a zymography assay, reaction of collagen IV with products of A2E photodegradation resulted in reduced cleavage by the matrix metalloproteinases MMP2 and MMP9. In conclusion, these mechanistic studies demonstrate a link between the photodegradation of RPE bisretinoid fluorophores and aging changes in underlying Bruch's membrane that can confer risk of age-related macular degeneration.